Spatially Variable CO2 Degassing in the Main Ethiopian Rift: Implications for Magma Storage, Volatile Transport, and Rift‐Related Emissions. (30th October 2017) - Hunt, Jonathan A.; Zafu, Amdemichael; Mather, Tamsin A.; Pyle, David M.; Barry, Peter H.
Abstract: Deep carbon emissions from historically inactive volcanoes, hydrothermal, and tectonic structures are among the greatest unknowns in the long‐term (∼Myr) carbon cycle. Recent estimates of diffuse CO2 flux from the Eastern Rift of the East African Rift System (EARS) suggest this could equal emissions from the entire mid‐ocean ridge system. We report new CO2 surveys from the Main Ethiopian Rift (MER, northernmost EARS), and reassess the rift‐related CO2 flux. Since degassing in the MER is concentrated in discrete areas of volcanic and off‐edifice activity, characterization of such areas is important for extrapolation to a rift‐scale budget. Locations of hot springs and fumaroles along the rift show numerous geothermal areas away from volcanic edifices. With these new data, we estimate total CO2 emissions from the central and northern MER as 0.52–4.36 Mt yr −1 . Our extrapolated flux from the Eastern Rift is 3.9–32.7 Mt yr −1 CO2, overlapping with lower end of the range presented in recent estimates. By scaling, we suggest that 6–18 Mt yr −1 CO2 flux can be accounted for by magmatic extension, which implies an important role for volatile‐enriched lithosphere, crustal assimilation, and/or additional magmatic intrusion to account for the upper range of flux estimates. Our results also have implications for the nature of volcanism in the MER. Many geothermal areas are found >10 km from the nearest volcanic center, suggesting ongoing hazards associated with regional volcanism. Plain Language Summary: The amount of carbon dioxide seeping out of the Earth's surface is poorly understood. Magma carries dissolved carbon dioxide from the deep earth toward the surface, where it is released and travels along fractures in the crust. This study attempts to quantify this phenomenon in central Ethiopia, where a continental rift is splitting one tectonic plate in two. In Kenya and Tanzania, a similar study suggested that the flow of carbon dioxide through the East African Rift was much larger than previously thought. We undertook new surveys and found that it varies greatly, which makes estimating a total flow through the rift very difficult. The distribution of hot springs and volcanic vents provides clues concerning where heat and carbon dioxide come to the surface—by compiling the locations of these features we were able to extrapolate from our surveys for a new estimate. Our results suggest that the East African Rift releases less carbon dioxide than was thought from Kenya and Tanzania, but still a substantial amount. If the rift does emit as much carbon dioxide as suggested, either more carbon is below the crust in East Africa than we thought or more magma is involved. Key Points: New gas surveys show that diffuse CO2 degassing in the Main Ethiopian Rift is highly variable, concentrated along faults in geothermal areas Locations of hot springs and fumaroles indicate numerous (∼14–20) geothermal areas some distance from major volcanic edifices Extrapolation from our data suggests a total diffuse CO2 flux from the Main Ethiopian Rift of 0.5–4.4 Mt yr −1 (whole Eastern Rift: 4–33 Mt yr −1 )